shl, a New Set of Arabidopsis Mutants with Exaggerated Developmental Responses to Available Red, Far-Red, and Blue Light - Pepper, Alan E.; Mi-seon Seong-Kim; Stephanie M. Hebst; Kathryn N. Ivey; Su-Jin Kwak; Denise E. Broyles (Plant physiology (Bethesda), 2001)
The interaction of light perception with development is the subject of intensive genetic analysis in the model plant Arabidopsis. We performed genetic screens in low white light-a threshold condition in which photomorphogenetic signaling pathways are only partially active-for ethyl methane sulfonate-generated mutants with altered developmental phenotypes. Recessive mutants with exaggerated developmental responses were obtained in eight complementation groups designated shl for seedlings hyperresponsive to light. shl1, shl2, shl5, and shl3 shl4 (double mutant) seedlings showed limited or no phenotypic effects in darkness, but showed significantly enhanced inhibition of hypocotyl elongation in low-white, red, far-red, blue, and green light across a range of fluences. These results reflect developmental hyper-responsiveness to signals generated by both phytochrome and cryptochrome photoreceptors. The shl11 mutant retained significant phenotypic effects on hypocotyl length in both the phyA mutant and phyB mutant backgrounds but may be dependent on CRY1 for phenotypic expression in blue light. The shl2 phenotype was partially dependent on PHYB, PHYA, and CRY1 in red, far-red, and blue light, respectively. shl2 and, in particular, shl1 were partially dependent on HY5 activity for their light-hyperresponsive phenotypes. The SHL genes act (genetically) as light-dependent negative regulators of photomorphogenesis, possibly in a downstream signaling or developmental pathway that is shared by CRY1, PHYA, and PHYB and other photoreceptors (CRY2, PHYC, PHYD, and PHYE).